The anti‐ageing effects of a natural peptide discovered by artificial intelligence. (20th July 2020) - Kennedy, K.; Cal, R.; Casey, R.; Lopez, C.; Adelfio, A.; Molloy, B.; Wall, A.M.; Holton, T.A.; Khaldi, N.
Abstract: Objective: As skin ages, impaired extracellular matrix (ECM) protein synthesis and increased action of degradative enzymes manifest as atrophy, wrinkling and laxity. There is mounting evidence for the functional role of exogenous peptides across many areas, including in offsetting the effects of cutaneous ageing. Here, using an artificial intelligence (AI) approach, we identified peptide RTE62G (pep_RTE62G), a naturally occurring, unmodified peptide with ECM stimulatory properties. The AI‐predicted anti‐ageing properties of pep_RTE62G were then validated through in vitro, ex vivo and proof of concept clinical testing. Methods: A deep learning approach was applied to unlock pep_RTE62G from a plant source, Pisum sativum (pea). Cell culture assays of human dermal fibroblasts (HDFs) and keratinocytes (HaCaTs) were subsequently used to evaluate the in vitro effect of pep_RTE62G. Distinct activities such as cell proliferation and ECM protein production properties were determined by ELISA assays. Cell migration was assessed using a wound healing assay, while ECM protein synthesis and gene expression were analysed, respectively, by immunofluorescence microscopy and PCR. Immunohistochemistry of human skin explants was employed to further investigate the induction of ECM proteins by pep_RTE62G ex vivo . Finally, the clinical effect of pep_RTE626 was evaluated in a proof of concept 28‐day pilot study. Results: In vitro testing confirmed that pep_RTE62G is an effective multi‐functional anti‐ageing ingredient. In HaCaTs, pep_RTE62G treatment significantly increases both cellular proliferation and migration. Similarly, in HDFs, pep_RTE62G consistently induced the neosynthesis of ECM protein elastin and collagen, effects that are upheld in human skin explants. Lastly, in our proof of concept clinical study, application of pep_RTE626 over 28 days demonstrated anti‐wrinkle and collagen stimulatory potential. Conclusion: pep_RTE62G represents a natural, unmodified peptide with AI‐predicted and experimentally validated anti‐ageing properties. Our results affirm the utility of AI in the discovery of novel, functional topical ingredients. Abstract : A natural peptide identified by Artificial Intelligence (AI) with anti‐ageing effects, pep_RTE626 induces the production extra cellular matrix proteins and exhibits clinical effects on wrinkle reduction and collagen stimulation. This study validates the utility of AI for novel cosmetic ingredient discovery. Résumé: OBJECTIF: À mesure que la peau vieillit, une altération de la synthèse des protéines de la matrice extracellulaire (ECM) et une action accrue des enzymes dégradantes se manifestent par une atrophie, des rides et un laxisme. Il existe de plus en plus de preuves du rôle fonctionnel des peptides exogènes dans de nombreux domaines, y compris pour compenser les effets du vieillissement cutané. Ici, en utilisant une approche d'intelligence artificielle (AI), nous avons identifié le peptide RTE62G (pep_RTE62G), un peptide naturel non modifié avec des propriétés de stimulation ECM. Les propriétés anti‐âge prédites par l'IA de pep_RTE62G ont ensuite été validées par des tests cliniques in vitro, ex vivo et de validation de principe. LES MÉTHODES: Une approche d'apprentissage en profondeur a été appliquée pour déverrouiller pep_RTE62G à partir d'une source végétale, Pisum sativum (pois). Des tests de culture cellulaire de fibroblastes dermiques humains (HDF) et de kératinocytes (HaCaTs) ont ensuite été utilisés pour évaluer l'effet in vitro de pep_RTE62G. Des activités distinctes telles que la prolifération cellulaire et les propriétés de production de protéines ECM ont été déterminées par des tests ELISA. La migration cellulaire a été évaluée à l'aide d'un test de cicatrisation des plaies, tandis que la synthèse des protéines ECM et l'expression des gènes ont été analysées, respectivement, par microscopie à immunofluorescence et PCR. L'immunohistochimie des explants de peau humaine a été utilisée pour approfondir l'induction des protéines ECM par pep_RTE62G ex vivo . Enfin, l'effet clinique de pep_RTE626 a été évalué dans une étude pilote de 28 jours de validation de principe. RÉSULTATS: Les tests in vitro ont confirmé que pep_RTE62G est un ingrédient anti‐âge multifonctionnel efficace. Dans HaCaTs, le traitement pep_RTE62G augmente de manière significative à la fois la prolifération et la migration cellulaire. De même, dans les HDF, pep_RTE62G a induit de manière cohérente la néosynthèse de la protéine ECM élastine et collagène, effets qui sont maintenus dans les explants de peau humaine. Enfin, dans notre étude clinique de preuve de concept, l'application de pep_RTE626 sur 28 jours a démontré un potentiel stimulant anti‐rides et collagène. CONCLUSION: pep_RTE62G représente un peptide naturel, non modifié avec des propriétés anti‐âge prédites par l'IA et validées expérimentalement. Nos résultats confirment l'utilité de l'IA dans la découverte de nouveaux ingrédients topiques fonctionnels.